A challenge for copyrights in the Digital Single Market: the editing of out-of-commerce works - Espín Alba, Isabel (UNIO – EU Law Journal, 2018)
This article makes a critical description of the statute of the licenses for the exploitation of works out-of-commerce envisaged in the Proposal for a Directive of the European Parliament and the Council on copyright in the Digital Single Market of September 14, 2016. In addition to the analysis of the precepts of the aforementioned Proposal, its main backgrounds are analysed, e.g., the Memorandum of Understanding on Key Principles on the Digitisation and Making Available of Out-of-Commerce Works, the French normative experience and the Soulier and Doke case (Judgment of the Court of Justice of the European Union of November 16, 2016).